Monolithic catalytic regenerative material based on carbon capture amine based absorbent catalytic regeneration and method of making and use thereof

CN122999165APending Publication Date: 2026-10-30TSINGHUA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510571526.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]然而,大多数关于催化CO2解吸的研究仍然停留在实验室阶段,催化剂以粉末的形式存在,而实际烟气碳捕集装置为整装填料塔,粉末催化剂无法在实际烟气碳捕集装置中稳定循环

Benefits of technology

[0033]与现有的技术相比,本发明的催化再生材料至少具有以下技术效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005388156570000011
    Figure HDA0005388156570000011
  • Figure HDA0005388156570000012
    Figure HDA0005388156570000012
  • Figure HDA0005388156570000021
    Figure HDA0005388156570000021
Patent Text Reader

Abstract

The application provides a kind of based on carbon capture amine absorption catalyst regeneration monolithic catalytic regeneration material and its preparation method and purposes.Catalyst regeneration material, characterized in that, including: carrier, the carrier includes metal material;And, carbon layer, the carbon layer is loaded on the surface of the carrier, wherein, the carbon layer has graphite phase structure, and the carrier is connected with carbon layer by covalent bond.The monolithic catalytic regeneration material provided by the application shows that after carbon activation, it has graphite phase structure, and has the characteristics of high activity and high stability.The monolithic catalytic regeneration material provided by the application has obvious CO2 desorption strengthening capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an integral catalytic regeneration material based on carbon capture amine absorbent catalytic regeneration, its preparation method and application, belonging to the field of greenhouse gas emission reduction and energy conservation. Background Technology

[0002] Current carbon capture technologies face challenges of high energy consumption and high cost. In particular, when using the amine absorption method, the nitrogen atoms in the amine form strong bonds with CO2, and traditional techniques struggle to precisely control the proton migration process. This results in CO2 desorption typically requiring high temperatures (110–130 °C), significantly increasing energy consumption and limiting the widespread application of the technology.

[0003] To address this issue, catalytic desorption technology has become an important approach to improve CO2 desorption efficiency. Developing highly active solid acid materials can effectively improve mass transfer, heat transfer, and kinetics in the CO2 desorption process, thereby promoting the development of low-energy carbon capture technologies. Regarding solid acid-catalyzed CO2 desorption processes, reference 1 proposes a method for preparing a FeZr@composite molecular sieve catalyst for the desorption of CO2-rich amine solutions. Related studies have shown that solid acid catalysts can act as acidic sites, significantly improving CO2 desorption efficiency. Research indicates that the application of solid acid catalysts can effectively improve CO2 desorption efficiency, thereby reducing the energy consumption and cost of carbon capture.

[0004] In addition, reference 2 discloses an α-Fe2O3 material for reducing carbon capture energy consumption, its preparation method, and its application. The α-Fe2O3 metal oxide catalyst is added to a CO2-enriched phase, and CO2 is desorbed by reaction at 90–95°C, achieving the regeneration of organic amines with low energy consumption.

[0005] However, most research on catalytic CO2 desorption remains in the laboratory stage, with catalysts existing in powder form. In contrast, actual flue gas carbon capture devices are prefabricated packed towers, making it impossible for powdered catalysts to circulate stably in practical systems. Furthermore, introducing solid powdered catalysts into carbon capture devices alters the gas-liquid mass transfer balance, posing a risk of blockage in the transmission pipelines and ultimately leading to decreased system stability.

[0006] Therefore, reducing the temperature and energy consumption of amine solvent regeneration, optimizing the matching effect between catalyst and carbon capture device, and developing and designing novel and efficient integrated packed catalysts for the carbon capture absorbent regeneration process have become urgent technical problems to be solved.

[0007] References:

[0008] Reference 1: CN110681413A

[0009] Reference 2: CN116332238A Summary of the Invention

[0010] The problem the invention aims to solve

[0011] In view of the technical problems existing in the prior art, the present invention provides an integral catalytic regeneration material with high activity and high stability, which can improve the carbon capture CO2 desorption kinetics, thereby reducing the energy consumption of the CO2 desorption process and the carbon capture operation cost, and achieving the purpose of energy conservation and emission reduction.

[0012] Furthermore, the present invention also provides a method for preparing an integral catalytic regeneration material, which is simple and easy to implement, uses readily available raw materials, and is suitable for mass production.

[0013] Solution for solving the problem

[0014] [1] An integral catalytic regeneration material based on carbon capture amine absorbent catalytic regeneration, comprising:

[0015] The carrier, the carrier comprising a metallic material; and,

[0016] A carbon layer, wherein the carbon layer is loaded on the surface of the carrier, wherein,

[0017] The carbon layer has a graphite phase structure, and the carrier and the carbon layer are connected by covalent bonds.

[0018] [2] The integral catalytic regeneration material according to [1] above, wherein the metal material includes metal plates and / or metal fillers.

[0019] [3] According to the integral catalytic regeneration material described in [2] above, wherein the thickness of the metal plate is 1-3 mm; and / or,

[0020] The metal packing includes one or more of the following: spring packing, bulk packing, and structured packing.

[0021] [4] The integral catalytic regeneration material according to any one of [1]-[3] above, wherein the carbon layer content in each square centimeter of the integral catalytic regeneration material is 0.1-5 mg.

[0022] [5] A method for preparing an integral catalytic regeneration material based on carbon capture amine absorbent catalytic regeneration according to any one of [1]-[4] above, comprising the step of loading a carbon layer on the surface of the carrier.

[0023] [6] The preparation method described in [5] above, wherein the preparation method includes the following steps:

[0024] The carrier was placed in a solution containing a carbon source to obtain a premix;

[0025] The premix is ​​subjected to a hydrothermal reaction to obtain a pretreated carrier;

[0026] The pretreated carrier is subjected to heat treatment to obtain an integral catalytic regeneration material.

[0027] [7] According to the preparation method described in [6] above, the mass concentration of the carbon source in the carbon source-containing solution is 1 to 20 wt%.

[0028] Preferably, the carbon source includes one or a combination of two or more of terephthalic acid, glucose, and dimethylimidazole.

[0029] [8] According to the preparation method described in [6] or [7] above, the temperature of the hydrothermal reaction is 100 to 120°C; the time of the hydrothermal reaction is 12 hours or more, preferably 12 to 96 hours.

[0030] [9] The preparation method according to any one of [6]-[8] above, wherein the temperature of the heat treatment is 800 to 1000°C, and the time of the heat treatment is 0.5 h or more, preferably 0.5 to 3 h.

[0031]

[10] The use of an integral catalytic regeneration material according to any one of [1]-[4] above in an amine carbon capture process.

[0032] The effects of the invention

[0033] Compared with existing technologies, the catalytic regeneration material of the present invention has at least the following technical advantages:

[0034] (1) The integral catalytic regeneration material provided by the present invention is in the form of a fully packed packing material, and the preparation method is simple.

[0035] (2) The integral catalytic regeneration material provided by the present invention shows that it has a graphite phase structure after carbon activation, and has the characteristics of high activity and high stability.

[0036] (3) The integral catalytic regeneration material provided by the present invention has a significant CO2 desorption enhancement capability.

[0037] (4) The catalytic regeneration material coupled with continuous absorption-desorption device and scale-up verification provided by the present invention, after stable operation test, proved that the catalyst can enhance the CO2 desorption and is easy to industrialize. Attached Figure Description

[0038] Figure 1 This invention illustrates a carbon capture device for continuous and stable operation of organic amine solution absorption-desorption of CO2, as described in Example 1 of the present invention.

[0039] Figure 2 A comparison diagram of Raman spectral characterization results of the monolithic catalytic regeneration material and the unmodified stainless steel sheet in Example 1 of the present invention is shown.

[0040] Figure 3 A comparison diagram showing the catalytic desorption results of the monolithic catalytic regeneration material and the unmodified stainless steel sheet in Example 1 of the present invention is shown.

[0041] Figure 4 This shows a pilot-scale device for the flue gas carbon capture device of Embodiment 2 of the present invention;

[0042] Figure 5 The diagram shows a comparison of the catalytic desorption results of the monolithic catalytic regeneration material and the unmodified stainless steel packing in Example 2 of the present invention. Detailed Implementation

[0043] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The term "exemplary" as used herein means "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior to or better than other embodiments.

[0044] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art should understand that the present invention can be practiced without certain specific details. In other instances, methods, means, apparatus, and steps well known to those skilled in the art have not been described in detail in order to highlight the spirit of the present invention.

[0045] Unless otherwise stated, all units used in this specification are international standard units, and all numerical values ​​and ranges appearing in this invention should be understood to include systematic errors that are unavoidable in industrial production.

[0046] In this specification, the word "may" has two meanings: to perform a certain process and not to perform a certain process.

[0047] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "implementation," etc., refer to specific elements (e.g., features, structures, properties, and / or characteristics) related to that embodiment, which are included in at least one of the embodiments described herein and may or may not be present in other embodiments. Furthermore, it should be understood that these elements may be combined in any suitable manner in various embodiments.

[0048] In this specification, the range of values ​​referred to as "value A to value B" refers to the range including the endpoint values ​​A and B.

[0049] <First Aspect>

[0050] A first aspect of the present invention provides an integral catalytic regeneration material based on carbon-capturing amine absorbent catalytic regeneration, comprising:

[0051] The carrier, the carrier comprising a metallic material; and,

[0052] A carbon layer, wherein the carbon layer is loaded on the surface of the carrier, wherein,

[0053] The carbon layer has a graphite phase structure, and the carrier and the carbon layer are connected by covalent bonds.

[0054] The integral catalytic regeneration material provided by this invention has a significant CO2 desorption enhancement capability. Therefore, the integral catalytic regeneration material of this invention can be used for the catalytic regeneration of amine absorbents in flue gas carbon dioxide capture.

[0055] carrier

[0056] This invention utilizes a carrier to obtain an integral catalytic regeneration material, eliminating the need for the catalyst to exist in powder form. This catalytic regeneration material can then be stably circulated within a flue gas carbon capture device. It does not alter the gas-liquid mass transfer balance, and there is no risk of blockage in the transmission pipeline, thus significantly improving system stability.

[0057] In some specific embodiments, the metal material includes a metal plate and / or metal filler; preferably, the metal material can be stainless steel. Specifically, the metal material can be one or a combination of two or more of 2205 stainless steel, 304 stainless steel, 314 stainless steel, and 316 stainless steel, preferably 316 stainless steel.

[0058] In this invention, the thickness of the metal plate can be 1-3mm, for example: 1.5mm, 2mm, 2.5mm, etc.

[0059] The present invention does not specifically limit the metal packing material; it can be any metal packing material commonly used in the art. Specifically, the metal packing material includes one or more combinations of spring packing, bulk packing, and structured packing.

[0060] Generally speaking, random packing, also known as bulk packing, refers to packing that is mainly randomly packed. This type of packing consists of granular materials with a certain shape and is also called granular packing. Generally, random packing can be classified into three types based on its shape: ring packing, saddle packing, and metal saddle ring packing. Specifically, ring packing can include Raschig ring packing, Pall ring packing, and stepped ring packing; saddle packing can include arc saddle packing, rectangular saddle packing, and improved rectangular saddle packing.

[0061] Structured packing, also known as structured corrugated packing, addresses the issue of random gas-liquid flow paths in haphazardly packed towers. While the packing itself is uniformly packed, this leads to channeling and other undesirable phenomena, reducing tower efficiency. Structured packing, on the other hand, is a type of packing arranged in a regular, uniform geometric pattern within the tower. This artificially defines the gas-liquid flow paths within the packing layer, reducing channeling and wall flow, significantly lowering pressure drop, and improving heat and mass transfer efficiency. Generally, structured packing can be categorized into wire mesh corrugated packing and plate corrugated packing based on its structure.

[0062] carbon layer

[0063] In this invention, the successful coating of a carbon layer with a graphite phase structure on the surface of a metal material enables the carbon element to be covalently bonded to the metal, thereby activating the metal on the surface of the metal material and improving its catalytic activity.

[0064] The carbon layer of the monolithic catalytic regeneration material of this invention has a graphite phase structure, thus exhibiting high activity and high stability. The graphite phase structure can also activate the metal on the surface of metallic materials, enhancing catalytic activity. Furthermore, the graphite phase structure possesses high stability, providing protection and improving the corrosion resistance of the stainless steel packing in organic solvents.

[0065] In some specific implementations, the carbon layer content in the monolithic catalytic regeneration material is 0.1-5 mg per square centimeter, for example: 0.5 mg, 1 mg, 1.5 mg, 2 mg, 2.5 mg, 3 mg, 3.5 mg, 4 mg, 4.5 mg, etc. In this case, the thickness of the carbon layer can be 0.2-5 μm. When the carbon layer content is 0.1-5 mg, its function is better achieved.

[0066] <Second aspect>

[0067] A second aspect of the present invention provides a method for preparing an integral catalytic regeneration material based on a carbon-capturing amine absorbent for catalytic regeneration, as described in the first aspect of the present invention, comprising the step of loading a carbon layer onto the surface of the support. The integral catalytic regeneration material provided by the present invention is in the form of a monolithic packing material, and its preparation method is simple.

[0068] In some specific implementations, the preparation method includes the following steps:

[0069] The carrier was placed in a solution containing a carbon source to obtain a premix;

[0070] The premix is ​​subjected to a hydrothermal reaction to obtain a pretreated carrier;

[0071] The pretreated carrier is subjected to heat treatment to obtain an integral catalytic regeneration material.

[0072] Furthermore, regarding the carrier, the present invention can separate and remove non-essential components from the carrier surface as needed. Specifically, alcohol solvents or water can be used to clean dust, grease, and other impurities from the carrier surface, followed by drying.

[0073] In some specific embodiments, the carbon source in the carbon source-containing solution has a mass concentration of 1 to 20 wt%, for example: 2 wt%, 4 wt%, 6 wt%, 8 wt%, 10 wt%, 12 wt%, 14 wt%, 16 wt%, 18 wt%, etc.

[0074] Specifically, the carbon source can be dissolved using an organic solvent to obtain a solution containing the carbon source. Specifically, the organic solvent can be one or a combination of two or more of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropionamide, N,N-diethylformamide, and N,N-diethylacetamide.

[0075] This invention does not impose a particular limitation on the mass ratio of carbon source to metal material, which can be set as needed. Generally, it is only necessary to ensure that the carbon source and iron sheet are in full contact during the hydrothermal process, so that the carbon layer content in each square centimeter of the integral catalytic regeneration material is 0.1-5 mg.

[0076] Furthermore, in this invention, the premix is ​​subjected to a hydrothermal reaction to obtain a pretreated carrier; the carbon source is attached to the surface of the metal material by a hydrothermal reaction, at which time the carbon source and the surface of the metal material are combined in the form of intermolecular forces, which serves as a pretreatment for the next heat treatment.

[0077] In some specific implementations, the temperature of the hydrothermal reaction is 100-120°C, for example: 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, etc.; the time of the hydrothermal reaction is more than 12 hours, preferably 12-96 hours, for example: 24 hours, 36 hours, 72 hours, 84 hours, etc.

[0078] Furthermore, the pretreated carrier is subjected to heat treatment to obtain an integral catalytic regeneration material. The inventors of this invention discovered that by thermal decomposition under high temperature and oxygen-free conditions, the carbon source and the metal material are bonded together in a covalent manner, thereby improving the adhesion stability of the carbon layer on the surface of the metal material.

[0079] In some specific embodiments, the heat treatment temperature is 800–1000°C, for example: 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, etc.; the heat treatment time is 0.5 hours or more, preferably 0.5–3 hours, for example: 1 hour, 1.5 hours, 2 hours, 2.5 hours, etc. Furthermore, the present invention can raise the temperature to the heat treatment temperature by a certain heating rate. Specifically, the heating rate can be 1–10°C / min, for example: 2°C / min, 4°C / min, 6°C / min, 8°C / min, etc.

[0080] <Third aspect>

[0081] A third aspect of the present invention provides the use of the monolithic catalytic regeneration material according to the first aspect of the present invention in an amine-based carbon capture process. The monolithic catalytic regeneration material of the present invention can be used in carbon capture processes to enhance the regeneration of amine absorbents and increase the CO2 desorption rate.

[0082] Example

[0083] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0084] Example 1

[0085] Reactor fabrication:

[0086] This embodiment uses a small-scale carbon capture device (such as an organic amine solution absorption-desorption CO2 continuously and stably operating CO2 capture device) Figure 1 As shown, the device can hold 300 mL of collecting liquid. The flow rate of the collecting liquid can be controlled by a liquid flow meter, allowing the intake of the saturated rich liquid and the output of the desorbed lean liquid. The flow rate of the collecting liquid can be controlled between 1-100 mL / min. The device can achieve absorption and desorption equilibrium, effectively evaluating the catalytic efficiency of the catalyst under stable operating conditions.

[0087] Material preparation:

[0088] 30g of terephthalic acid was dissolved in 400mL of N,N-dimethylformamide to obtain solution A, which was then placed in a hydrothermal reactor. A 1mm thick 316 stainless steel sheet was cut into pieces 20cm long and 10cm wide, cleaned and dried with ethanol and ultrapure water, and then placed in solution A to obtain a premix. The premix was then placed in a hydrothermal reactor and hydrothermally reacted at 110℃ for 24 hours. After the hydrothermal reactor cooled to room temperature, the pretreated steel sheet was removed and dried.

[0089] The pretreated steel sheets obtained above were placed in a tube furnace, with inert nitrogen gas as the protective atmosphere, and heated from 30°C to 900°C at a heating rate of 5°C / min, held for 1 hour, and then allowed to cool naturally. The final product is surface-carbon-activated modified stainless steel, i.e., an integral catalytic regeneration material, wherein the carbon layer content is approximately 1 mg per square centimeter of the integral catalytic regeneration material.

[0090] Raman spectroscopy characterization:

[0091] After carbon activation, the surface of the 316 stainless steel sheet is coated with a layer of carbon, such as... Figure 2 As shown, based on the Raman spectroscopy characterization results, the carbon layer on the surface of the steel sheet has a graphite phase (I0). D Peak structure.

[0092] Activity experiment:

[0093] The integral catalytic regeneration material was placed in the aforementioned carbon capture device to study its effect on CO2 desorption. As a control, blank experiments and desorption experiments with unmodified stainless steel sheets were conducted, and the results are as follows: Figure 3 As shown.

[0094] Depend on Figure 3 It can be seen that the unmodified steel sheet did not promote catalytic desorption. After the system reached equilibrium, the CO2 desorption rate per unit time did not change significantly, remaining at around 30 mL / min, proving that stainless steel had neither promoting nor inhibiting effect on the carbon capture system. However, after using the monolithic catalytic regeneration material of Example 1, the catalytic desorption effect was significant. After the system reached equilibrium, the desorption rate reached around 100 mL / min, which is more than three times higher than the original rate.

[0095] Example 2

[0096] Material preparation:

[0097] 30g of terephthalic acid was dissolved in 350mL of N,N-dimethylformamide to obtain solution A, which was then placed in a hydrothermal reactor. Spring packing was placed in solution A to obtain a premix, the total volume of which was 400mL. Subsequently, the premix was placed in the hydrothermal reactor and hydrothermally reacted at 110℃ for 24h to obtain pretreated spring packing. This process ensured that the spring packing was completely submerged in the solution. After the hydrothermal reactor cooled to room temperature, the pretreated spring packing was removed and dried. The spring packing was made of 316 stainless steel Sierra rings with a diameter of 4mm.

[0098] The pretreated spring packing obtained above was placed in a tube furnace, with inert nitrogen gas as the protective atmosphere, and heated from 30°C to 900°C at a heating rate of 5°C / min, held for 1 hour, and then allowed to cool naturally. The resulting stainless steel packing with surface carbon activation modification, i.e., an integral catalytic regeneration material, was obtained, wherein the carbon layer content in each square centimeter of the integral catalytic regeneration material is approximately 1 mg.

[0099] Catalytic desorption unit:

[0100] To verify the feasibility and reliability of this design, a pilot-scale flue gas carbon capture device was designed and developed based on actual carbon capture processes (such as...). Figure 4 As shown in the figure, the device can process 20L of flue gas per minute, and the collection liquid circulation rate is 4L / h. Both the absorption tower and the desorption tower are stainless steel packed towers. In this embodiment, the stainless steel packing before and after carbon activation is loaded into the desorption tower as variables to study the effect of carbon-activated stainless steel on the desorption side of carbon capture of CO2.

[0101] Activity experiment:

[0102] Absorption tower: CO2 absorption experiments were conducted at 40℃. A 30% (w / w) ethanolamine solution was used as the collection liquid at a flow rate of 3 L / h, and the CO2 volume fraction in the flue gas was 12% at a flow rate of 15 L / min. The CO2 concentration at the absorber outlet was measured using an online flue gas analyzer.

[0103] Desorption tower: The desorption tower is heated using a constant-temperature oil bath, with regeneration temperatures controlled at 95℃, 105℃, and 115℃ respectively. The CO2 flow rate at the outlet of the desorption tower is monitored in real time using a mass flow meter.

[0104] The original stainless steel packing in the desorption tower was replaced with the monolithic catalytic regeneration material prepared in Example 2. The carbon capture efficiency before and after the replacement was compared, and the test results are as follows: Figure 5 As shown.

[0105] Depend on Figure 5 As can be seen, compared with non-catalytic conditions, the monolithic catalytic regeneration material prepared in Example 2 can improve the carbon capture efficiency by 7%, 13%, and 10% at 95℃, 105℃, and 115℃, respectively. Therefore, the catalytic regeneration material of this invention exhibits good catalytic activity.

[0106] It should be noted that although the technical solution of the present invention has been described with specific examples, those skilled in the art will understand that the present invention should not be limited thereto.

[0107] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or technical improvements to the embodiments in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. A monolithic catalytic regeneration material based on carbon-capturing amine-based absorbent catalytic regeneration, characterized in that, include: The carrier includes a metallic material; as well as, A carbon layer, wherein the carbon layer is loaded on the surface of the carrier, wherein, The carbon layer has a graphite phase structure, and the carrier and the carbon layer are connected by covalent bonds.

2. The integral catalytic regeneration material according to claim 1, characterized in that, The metallic material includes metal plates and / or metal fillers.

3. The integral catalytic regeneration material according to claim 2, characterized in that, The thickness of the metal plate is 1-3 mm; and / or, The metal packing includes one or more of the following: spring packing, bulk packing, and structured packing.

4. The integral catalytic regeneration material according to any one of claims 1-3, characterized in that, The carbon layer content in each square centimeter of the monolithic catalytic regeneration material is 0.1-5 mg.

5. A method for preparing an integral catalytic regeneration material based on carbon-capturing amine-based absorbent catalytic regeneration according to any one of claims 1-4, characterized in that, This includes the step of loading a carbon layer onto the surface of the carrier.

6. The preparation method according to claim 5, characterized in that, The preparation method includes the following steps: The carrier was placed in a solution containing a carbon source to obtain a premix; The premix is ​​subjected to a hydrothermal reaction to obtain a pretreated carrier; The pretreated carrier is subjected to heat treatment to obtain an integral catalytic regeneration material.

7. The preparation method according to claim 6, characterized in that, In the carbon source-containing solution, the mass concentration of the carbon source is 1-20 wt%. Preferably, the carbon source includes one or a combination of two or more of terephthalic acid, glucose, and dimethylimidazole.

8. The preparation method according to claim 6 or 7, characterized in that, The temperature of the hydrothermal reaction is 100-120°C; the time of the hydrothermal reaction is 12 hours or more, preferably 12-96 hours.

9. The preparation method according to any one of claims 6-8, characterized in that, The heat treatment temperature is 800–1000°C, and the heat treatment time is 0.5 h or more, preferably 0.5–3 h.

10. The use of the integral catalytic regeneration material according to any one of claims 1-4 in an amine-based carbon capture process.

Citation Information

Patent Citations

  • Preparation method of nano FeZr@composite molecular sieve catalyst for desorption of CO2-rich amine solution

    CN110681413A

  • Alpha-Fe2O3 material for reducing carbon capture energy consumption as well as preparation method and application of alpha-Fe2O3 material

    CN116332238A